Effect of salicylic acid on seedling of Vigna radiata L. under salt stress - Aldera, Mona Abdullah; Alsahli, Abdulaziz Abdullah; Alwatban, Ahlam Abdullah; Khalofah, Ahlam (Journal of natural sciences, life and applied sciences, 2022)
The mung bean plant (Vigna radiata L.) belongs to the leguminous family. It has high economic importance as it is used to fix nitrogen in the soil and is used in the nutrition of both humans and livestock. Plant morphology is decisively affected by salt stress, which leads to a marked decrease in plant growth and metabolic processes. Salicylic acid SA was used to mitigate the harmful effects of salt stress on the plant, where the tolerance of seedlings of Vigna radiata L. to different concentrations of NaCl was studied as follows (0, 100, 200, 300) mM, and the activity of SA at concentrations ( 2, 1, 0) ppm to mitigate the harmful effects of salinity at the germination stage in vitro in Petri dishes, and in the growth room in plastic pots, The full random sectors (RCBD) were followed by a one-time split-plot where SA coefficients represented the main plot and NaCl represented the renegade sector (sub-plot) by three bis. Salinity decreased germination percentage and growth parameters (root and stem length, plant height, number of leaves per plant, leaf area, root and stem fresh and dry weight, as well as relative water content). However, pre-soaking treatment with 2 ppm concentration of SA showed Vigna radiata L. seeds had an effective effect in improving growth criteria in the presence and absence of NaCl, while the concentration of 1 ppm of SA had no clear effect, may be due to the ability of SA to increase cell division in the plant’s meristem areas, regulate osmotic pressure and hormonal balance, as well as activate photosynthesis.